A efetividade das unidades de conservação na sustentabilidade da paisagem. - Xavier, Erick Caldas (2015)
Demonstration of the significant regeneration of thre natural areas (Environmental Protection Area of the Ilhas e Várzeas do Rio Paraná, Ilha Grande National Park and Várzeas do Rio Ivinhema State Park) after the creation of protected areas, without harming the local economy, can contribute to the deconstruction of the paradigm that protection of nature is incompatible with economic development. Through a SIG analysis of a period of 30 years, it can be seen that after decades of degradation, the past 20 years saw significant increase in forest and regeneration areas in the three conservation areas, whilst agriculture and Gross Domestic Product of the region increased. In addition to protecting biodiversity and natural resources, when conservation areas provide shelter to land in regeneration, they can provide important ecosystems which support life thus contributing to the sustainability of the landscape and human development.